2002
DOI: 10.1016/s0165-5876(02)00009-5
|View full text |Cite
|
Sign up to set email alerts
|

Decreased serum and pharyngeal antibody levels specific to streptococcal lipoteichoic acid in children with recurrent tonsillitis

Abstract: Objective: Streptococcus (S.) pyogenes is common causes of primary as well as recurrent tonsillitis (RT). Lipoteichoic acid (LTA) has been proposed as a possible candidate for vaccine formulation against streptococcal infections, because LTA is a common constituent of streptococci and the antibody to LTA inhibits bacterial attachment to epithelial cells in vitro. Streptolysin-O and streptococcal whole cell body are highly immunogenic and the antibodies to these antigens are reported to be better parameters for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…However, this is still preliminary and there is a number of problems to be dissolved. For example, we previously demonstrated decreased pharyngeal IgA antibody levels to streptococcal LTA in children with recurrent tonsillitis [10], suggesting that pharyngeal antibody response to LTA vaccine may be reduced in those children. The CT-B used as an adjuvant in this study is toxic in humans.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, this is still preliminary and there is a number of problems to be dissolved. For example, we previously demonstrated decreased pharyngeal IgA antibody levels to streptococcal LTA in children with recurrent tonsillitis [10], suggesting that pharyngeal antibody response to LTA vaccine may be reduced in those children. The CT-B used as an adjuvant in this study is toxic in humans.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, we demonstrated decreased serum IgG and pharyngeal IgA antibody levels specific to streptococcal LTA in young children with RT [10]. This immunologic failure may be potential cause of RT in childhood.…”
Section: Introductionmentioning
confidence: 86%
“…Lipoteichoic acid has been linked to a variety of bacterial cellular functions, such as membrane elasticity and porosity, trafficking of molecules, anchoring of wall proteins, and determination of net charge and surface hydrophobicity (25). Lipoteichoic acids from several gram-positive bacteria have been shown to engage in interactions with Tolllike receptor 2 (12), and LTA is known to participate in attachment to epithelial and endothelial surfaces and to biomaterials (3,9,36) and is also involved in cell invasion (3). Thus, antibodies to LTA could inhibit a variety of bacterial functions or host responses.…”
Section: Discussionmentioning
confidence: 99%
“…This may explain, at least in part, why these patients have persistent infection. In line with this hypothesis, concentrations of IgG antibodies to streptococcal and staphylococcal lipoteichoic acids are reported significantly lower in the serum of children with RT than in that of those without RT ; the titers of these antibodies correlate inversely with number of episodes of tonsillitis . Furthermore, it has been shown that active infection with S. aureus compromises induction of both humoral and cell‐mediated immunity .…”
Section: Discussionmentioning
confidence: 73%